Pemberian SABU (Serum Anti-Bisa Ular) untuk Kasus Gigitan Ular Awitan Lama dengan Komplikasi Disseminated Intravascular Coagulation (DIC) - Simangunsong, Dedy Kristofer; Hadiki Habib; Simbolon, Eirene (PT Kalbe Farma Tbk., 2024)
Background: Snakebite is a neglected disease in subtropical and tropical countries in Asia, Africa, and Latin America. Snakebite is one of the most common venomous animal bites in the world. Case: A 34-year-old male presented with a history of snakebite two days before with a swollen left gluteus and spontaneous gum bleeding. At the emergency room, the patient was fully conscious with blood pressure of 120/80 mmHg, temperature of 36.8oC, pulse rate of 80 beats per minute, and respiration rate of 18 times per minute. Blood studies showed prolonged prothrombin time (PT) and activated partial thromboplastin time (aPTT), leucocytosis, thrombocytopenia, low hemoglobin, and elevated renal function test. The patient's condition was improved after administration of anti-snake venom, vitamin K injection, transfusion of fresh frozen plasma and packed red cells. He was discharged after three days of hospital stays. Conclusion: Antivenom is the only specific antidote to snake venom; in Indonesia, there is only one local antivenom, commonly known as SABU (serum anti-bisa ular). Inappropriate use of antivenom should be strongly discouraged. Administration of the antivenom should be accompanied by preparedness for anaphylaxis risk.